Culture Medium Supplements Derived from Human Platelet and Plasma: Cell Commitment and Proliferation Support - Anita Muraglia; Van Thi Nguyen; Marta Nardini; Massimo Mogni; Domenico Coviello; Beatrice Dozin; Paolo Strada; Ilaria Baldelli; Matteo Formica; Ranieri Cancedda; Ranieri Cancedda; Maddalena Mastrogiacomo (Frontiers in Bioengineering and Biotechnology, 2017)
Present cell culture medium supplements, in most cases based on animal sera, are not fully satisfactory especially for the in vitro expansion of cells intended for human cell therapy. This paper refers to (i) an heparin-free human platelet lysate (PL) devoid of serum or plasma components (v-PL) and (ii) an heparin-free human serum derived from plasma devoid of PL components (Pl-s) and to their use as single components or in combination in primary or cell line cultures. Human mesenchymal stem cells (MSC) primary cultures were obtained from adipose tissue, bone marrow, and umbilical cord. Human chondrocytes were obtained from articular cartilage biopsies. In general, MSC expanded in the presence of Pl-s alone showed a low or no proliferation in comparison to cells grown with the combination of Pl-s and v-PL. Confluent, growth-arrested cells, either human MSC or human articular chondrocytes, treated with v-PL resumed proliferation, whereas control cultures, not supplemented with v-PL, remained quiescent and did not proliferate. Interestingly, signal transduction pathways distinctive of proliferation were activated also in cells treated with v-PL in the absence of serum, when cell proliferation did not occur, indicating that v-PL could induce the cell re-entry in the cell cycle (cell commitment), but the presence of serum proteins was an absolute requirement for cell proliferation to happen. Indeed, Pl-s alone supported cell growth in constitutively activated cell lines (U-937, HeLa, HaCaT, and V-79) regardless of the co-presence of v-PL. Plasma- and plasma-derived serum were equally able to sustain cell proliferation although, for cells cultured in adhesion, the Pl-s was more efficient than the plasma from which it was derived. In conclusion, the cells expanded in the presence of the new additives maintained their differentiation potential and did not show alterations in their karyotype.